Compositional analysis on ancient bricks from Candi Sungai Mas (Site 32/34), Bujang Valley, Kedah - Ramli, Zuliskandar; Nik Abd. Rahman, Nik Hassan Shuhaimi; Jusoh, Adnan; Hussein, Mohd Zobir (Science Publications, 2012)
Problem statement: The significance of Kampung Sungai Mas as an importance archaeology site in Lembah Bujang was revealed in the year 1979 when a cannel was built along Kampung Sungai Mas area. During the construction study of this cannel, thousands of ceramic pieces from India, Middle East, China, Southeast Asia and Europe was discovered, pieces of glasses from Middle East and Europe, stone and glasses beads from Middle East, India and local also pieces and blocks of construction substance from brick and mud stone or slate stone. An inscription also was discovered by one of the villagers when the cannel construction was in progress and this inscription sized estimated 46×23 cm produced from mud stone and relative estimation based on Pallawa script on the stone and can be dated around 56th century AD. Scientific study done onto Candi Sungai Mas (Site32/34) ancient brick was prominent for archaeology data because since the very beginning, archeologist who was doing research in Kampung Sungai Mas questioned whether the brick discovered was produced by the local society or brought from other area. Approach: Technique used was X-Ray Fluorescence Spectroscopy (XRF) and X-Ray Diffraction (XRD) technique. X-ray Fluorescence Spectroscopy (XRF) can determine the major and trace elements of the bricks whilst X-Ray Diffraction (XRD) can determine the mineral content of the bricks. Results: Compositional analysis on Candi Sungai Mas (Site 32/34) showed that open firing technique was used to burnt the bricks and that there were two different raw sources used to produce the brick at Kampung Sungai Mas. The raw material used for making the bricks were taken from Bujang River and Muda River basin. Conclusion: It can be concluded here that the protohistory society at Kampung Sungai Mas especially Malay society has succeeded to conquer knowledge and technology on making the brick and showed that we have developed long ago.